A STUDY TO DISCOVERING THE DOMINANT FACTOR OF EMPLOYEE ENGAGEMENT CASE STUDY: RUMAH BATIK KOMAR CIGADUNG - Azania, Bela; Febriansyah, Hary (Journal of Business and Management, 2017)
Abstract.Employee engagement become popular because some survey shows that employee engagement can drive production process effectiveness also a good engagement will increase company reputation. The condition of employee engagement divided into three; actively engaged, not engaged and actively disengaged. Actively disengaged employee is dangerous because they can spread the negativity to the others. Impact of negativity can disrupt the production lines, especially in creative industry business that have continued production process. Another loss for the business is also when their well-trained new employee decided to resign because not engage.  The objective of this research are find the factors of employee engagement and define the dominant factor. To achieve the objectives, using factor analysis to define the factor from twelve question of Gallup Q12. The data collection method is quantitative used questionnaire and literature review studying. Literature are about the employee engagement case and recommendation. Subject of this research is staff in marketing and production division Rumah Batik Komar Cigadung, Bandung. From the analysis, there are two factor that influence employee engagement; employee recognition and employee development. After doing the point biserial correlation, employee recognition is the dominant factor that influence employee engagement in Rumah Batik Komar. Therefore, this research give some recommendation to maintain and improve employee recognition. Keywords:  Creative Culture Industry, Dominant Factor of Engagement, Employee Engagement, Gallup Q12, Rumah Batik Komar